Internal Communication as a Catalyst for Employee Engagement and Performance in Paramilitary Organisations - Maiwada, Abdullahi Aliyu; Oshionebo, Barth (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2024)
In today's global landscape, organisations have shifted from conventional communication approaches to comprehensive strategies that are focused on engaging and motivating their employees. This change highlights the critical function of strategic internal communication, which is still emerging but increasingly important field of study and practice in business and private sectors. The modern workplace has seen a change in employees' roles, with workers taking on more duties previously related to public relations. This paper examines internal communication as a catalyst for employee engagement and performance in paramilitary organisations. The paper is based on the conceptual framework, which allowed for the evaluation of the existing knowledge for the purpose of relevance, consistency, replication, and refutation. This paper accepts the theoretical assumptions of the Two-Way Symmetrical Theory of Public Relations, which is based on a dual exchange of ideas. The paper argues that paramilitary organisations, like the Nigeria Customs Service, have internal communication procedures that are different from traditional corporate organisational structures. This discrepancy is distinctively noticeable given the agency's diverse responsibilities in revenue generation, trade facilitation, and the suppression of smuggling. The paper concludes that employee participation and job satisfaction mediated the relationship between internal communication and employees’ job performance.